2021
DOI: 10.32637/orli.v51i1.412
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Neck Nodule Size with Body Mass Index and Karnofsky Status Before and After Neoadjuvant Cisplatin and 5-Fluorouracil Chemotherapy in Nasopharyngeal Carcinoma Type 3 Patients

Abstract: Introduction: Nasopharyngeal carcinoma (NPC) is a malignancy arising from the nasopharyngeal epithelium, usually present in the Rosenmüller fossa. NPC is a cancer of the head and neck that is most common in East Asia and Southeast Asia, including in Indonesia. The main therapeutic for NPC is radiotherapy. Neoadjuvant chemotherapy reduces the local spread of advanced NPC, eradication of micrometastases, and improved local control. Neoadjuvant chemotherapy's effectiveness can be assessed by changes in the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…18,19 Administration of chemotherapy with an optimal dose and the right duration will be able to maintain a low NLR value, whereas a low NLR during neoadjuvant chemotherapy will provide a better response to therapy. 20 Research conducted by Efranto et al 21 , showed that there was a reduction or reduction in the size of the neck nodules in patients with Cisplatin and 5-FU neoadjuvan chemotherapy with significant results. This was corroborated by several researches reported that neoadjuvant chemotherapy had a higher potential for reducing distant metastatic failure, especially in patients with extensive nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Administration of chemotherapy with an optimal dose and the right duration will be able to maintain a low NLR value, whereas a low NLR during neoadjuvant chemotherapy will provide a better response to therapy. 20 Research conducted by Efranto et al 21 , showed that there was a reduction or reduction in the size of the neck nodules in patients with Cisplatin and 5-FU neoadjuvan chemotherapy with significant results. This was corroborated by several researches reported that neoadjuvant chemotherapy had a higher potential for reducing distant metastatic failure, especially in patients with extensive nodules.…”
Section: Discussionmentioning
confidence: 99%
“…This was corroborated by several researches reported that neoadjuvant chemotherapy had a higher potential for reducing distant metastatic failure, especially in patients with extensive nodules. The research by Al-Amro et al, cited by Efranto et al 21 , assessed the effectiveness of neoadjuvant chemotherapy Cisplatin and Epirubicin followed by Cisplatin chemotherapy along with radiotherapy in 110 patients with advanced NPC showed complete remission and partial remission achieved in 87 subjects (79%) and 23 subjects (21%) respectively.…”
Section: Discussionmentioning
confidence: 99%